2020
DOI: 10.1053/j.gastro.2019.11.302
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Mutations in Armadillo Repeats 5 and 6 of β-Catenin Reduce Binding to APC, Increasing Signaling and Transcription of Target Genes

Abstract: Supplementary Figure 4. AXIN2 RNA expression in b-catenin S37F and K335I knock-in clones. The top panels show the AXIN2 expression levels determined by qRT-PCR (mean ± standard deviation, n ¼ 5) for all analyzed clones. The bottom panels show the results for K335I knock-in clones only. All expression levels are depicted relative to the housekeeping gene GAPDH. Data are presented as mean ± standard deviation. **P < .01; ***P < .001; ****P < .0001. CTR, control. March 2020 Armadillo Repeat 5/6 Mutations of b-Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Interestingly, these same groups also show an enrichment in CTNNB1 mutations within armadillo repeats 5 and 6 (i.e. K335, W383, N387), for which we have recently unequivocally shown that they are efficient inducers of HCC development in mice, associated with a weak but significant activation of β-catenin signaling 8 . Expression profiling of tumor tissues has the inherent shortcoming that average expression is determined of a heterogeneous group of cells, including contaminating normal cells.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Interestingly, these same groups also show an enrichment in CTNNB1 mutations within armadillo repeats 5 and 6 (i.e. K335, W383, N387), for which we have recently unequivocally shown that they are efficient inducers of HCC development in mice, associated with a weak but significant activation of β-catenin signaling 8 . Expression profiling of tumor tissues has the inherent shortcoming that average expression is determined of a heterogeneous group of cells, including contaminating normal cells.…”
Section: Discussionmentioning
confidence: 77%
“…AXIN1-mutant HCCs predominantly show an exclusive membranous β-catenin staining 10 12 , 15 , indeed suggesting that there is no nuclear signaling. However, this is also observed in tumors carrying oncogenic CTNNB1 mutations within the armadillo repeats and a subset of S45-mutant cancers 8 , 43 , while these clearly lead to enhanced signaling. Thus, although nuclear accumulation of β-catenin is a reliable predictor of active signaling, its absence does not exclude that a low level of biologically relevant signaling is active 44 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Despite evident promise, immune therapy for this disease remains unsatisfactory [ 47 , 48 , 49 , 50 ]. Importantly, the genetic basis of the disease is now partially understood [ 51 , 52 , 53 ] as is the resulting cell biology. Intrinsic factors such as stem cell markers (i.e., LGR5 [ 54 ]) and extrinsic factors including the surrounding microenvironment (e.g., bacterial and toxic drivers of mutagenesis [ 55 ] and cancer associated fibroblasts supporting cancer growth [ 56 ]) contribute to hepatocellular carcinoma growth.…”
Section: Liver Cancermentioning
confidence: 99%